An Innovative Postgradaute Programme in Artificial Intelligence for the Industry 5.0 by 2030 - Henry, Rabinder (University News, 2025)
The era of rapid industrialization in the late 19th century saw the emergence of large factories, complex systems for distributing goods, integrated logistics and transport, and the offices required for administrative functions.
ISDI